Escape Rooms for Learning: A Case Study of a Collaborative, Interdisciplinary Project - Holly Surbaugh; Melissa Jones (Journal of New Librarianship)
As the popularity of escape rooms as a form of entertainment has increased, so has interest in their potential as an instructional innovation. This case study documents a two-year, multiphase project piloting two approaches to using escape rooms for learning. During the first phase (“Escape Room as an Assignment”), instruction librarians embedded with two classes to develop functional inputs for the second phase (“Escape Room as a Classroom/Lab”), which entailed using a library escape room to teach information literacy. This paper contributes to understanding of how academic libraries can support faculty who wish to experiment with incorporating escape room elements into their curriculum while identifying the affordances conveyed by this unique educational environment. It also theorizes how escape rooms for learning might adapt to a variety of subject areas.